2017
DOI: 10.3389/fnmol.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the Interaction of APP and Lipoprotein Receptors

Abstract: The biological fates of the key initiator of Alzheimer’s disease (AD), the amyloid precursor protein (APP), and a family of lipoprotein receptors, the low-density lipoprotein (LDL) receptor-related proteins (LRPs) and their molecular roles in the neurodegenerative disease process are inseparably interwoven. Not only does APP bind tightly to the extracellular domains (ECDs) of several members of the LRP group, their intracellular portions are also connected through scaffolds like the one established by FE65 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 316 publications
(438 reference statements)
0
52
0
Order By: Relevance
“…Yet another possibility is that ADAMTS4 is secreted by oligodendrocytes and taken up by neurons through endocytosis, leading to the processing of APP by ADAMTS4 in intracellular vesicular compartments. Indeed, in cartilage, it has been demonstrated that extracellular ADAMTS4 can be internalized via low density lipoprotein receptor-related protein (LRP1), which is abundantly expressed in neurons [57,81]. Further studies are required to clarify this issue, but all three of these possibilities conform to our immunohistochemical detection of Aβ4-x peptides in white matter structures and their co-localization with APP in fiber tracts of 5xFAD mice (see below).…”
Section: Discussionmentioning
confidence: 60%
“…Yet another possibility is that ADAMTS4 is secreted by oligodendrocytes and taken up by neurons through endocytosis, leading to the processing of APP by ADAMTS4 in intracellular vesicular compartments. Indeed, in cartilage, it has been demonstrated that extracellular ADAMTS4 can be internalized via low density lipoprotein receptor-related protein (LRP1), which is abundantly expressed in neurons [57,81]. Further studies are required to clarify this issue, but all three of these possibilities conform to our immunohistochemical detection of Aβ4-x peptides in white matter structures and their co-localization with APP in fiber tracts of 5xFAD mice (see below).…”
Section: Discussionmentioning
confidence: 60%
“…In addition to APP, FE65 interacts with LRP1 via its PTB1 domain. It is proposed that LRP1/FE65/APP promotes amyloidogenic processing of APP by increasing endocytosis that makes APP more accessible to the endosomal BACE1 and γ-secretase 26 . The availability of FE65 for recruiting LRP1 and APP may be crucial for the formation of the trimeric complex.…”
Section: Discussionmentioning
confidence: 99%
“…Most LRP receptors have in the intracellular region at least one NPxY-(endocytosis) motif. However, LRP5/6 are lacking this motif (105). Mutations in three members of the LRP family, namely, LRP4, LRP5, and LRP6, are reported to result in rare skeletal disorders (51,106,107).…”
Section: Lrp Receptorsmentioning
confidence: 99%